Who moved my cheese? : an amazing way to deal with change in your work and in your life - Johnson, Spencer (New York : Putnam, 1998)
A parable that teaches lessons about change and how to deal with it.
Parts of all of us -- The story behind the story / by Kenneth Blanchard -- A gathering: Chicago -- The story of Who Moved My Cheese?. Four characters ; Finding cheese ; No Cheese! ; The mice: Sniff & Scurry ; The littlepeople: Hem & Haw ; Meanwhile, back in the maze ; Getting beyond fear ; Enjoying the adventure ; Moving with the cheese ; The handwriting on the wall ; Tasting new cheese ; Enjoying change! -- A discussion: later that same day.
Also issued online.
Keywords: Change (Psychology); Life change events -- Psychological aspects; Adaptation, Psychological; Life Change Events; Change (Psychology.); Changement (Psychologie); Change (Psychology); 00079765; 00422745